A high temperature polymer of phthalonitrile‐substituted phosphazene with low melting point and good thermal stability. Issue 39 (3rd July 2015) - Zhao, Fenghua; Liu, Ruojin; Yu, Xiaoyan; Naito, Kimiyoshi; Qu, Xiongwei; Zhang, Qingxin
ABSTRACT A phthalonitrile‐substituted phosphonitrilic monomer has been synthesized from phosphonitrilic chloride trimer and then polymerized with addition of 4‐(hydroxylphenoxy)phthalonitrile (HPPN). The chemical structures of the phosphonitrilic monomer and polymer were characterized by Fourier Transform Infrared spectroscopy (FT‐IR) and proton Nuclear Magnetic Resonance spectroscopy (1H NMR). Curing behaviors and thermal stabilities of the polymer were investigated through differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Analysis showed that the monomer has large processing temperature window and good thermal stability. Apparent activation energy, initial curing temperature (Ti), curing temperature (Tp), and termination curing temperature (Tf) of the phosphonitrilic polymer were explored. Dynamic mechanical analysis (DMA), glass transition temperature (Tg) were studied, and limiting oxygen index (LOI) were estimated from the van Krevelen equation, which indicates the polymer process high modulus and good flame retardance. Micro‐scale combustion calorimetry (MCC) was also used for evaluating the flammability of the polymers. Postcuring effects were explored, showing excellent thermal and mechanical properties with postcuring. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42606.